7E.004 Violence reduction units: public health approach to preventing violence (England and Wales). (14th March 2021) - Quigg, Zara; Timpson, Hannah; Butler, Nadia; Millings, Matthew; Harrison, Rebecca
Abstract : Background: In 2018, UK Government published its Serious Violence Strategy in response to increases in knife and gun crime. The strategy declared a call to action for partners across different sectors to collaborate and adopt a whole system public health approach to preventing serious violence. In June 2019, 18 areas were provided with funding to establish violence reduction units (VRUs), bringing together police, local government, health, community leaders and other key partners with a specific intent to tackle violence and its underlying causes. This study aims to identify the development and implementation of VRUs during 2019/20, including facilitating and moderating factors, and outcomes and impacts. Methods: The study focuses on three VRU areas across England and Wales (population~5 million). Methods include interviews (n~40) and engagement (e.g. via workshops; n~200) with a range of stakeholders (e.g. VRU team members/advisors; intervention programme commissioners/delivers), analyses of programme documentation, and observation of programme delivery. Results: Initial findings illustrate that the three VRUs are implementing a place-based approach to violence prevention, have developed a problem profile and strategy for future prevention activity (in the short and long-term), and implemented various interventions to prevent and respond to violence. Interventions target system change, and also consider a life course public health perspective. Conclusion/Learning Outcomes: Key learning from the initial development and implementation of the VRUs will be presented, considering the principles of the public health approach and UK government guiding principles for VRUs: collaboration; co-production; cooperative in data and intelligence sharing; counter-narrative development; and community consensus.